Peran Kepuasan Kerja dalam Perilaku Quiet Quitting pada Karyawan Generasi Z - Mohamad Rizky al Fazri; Diah Sofiah; Yanto Prasetyo (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract Quiet quitting is a workplace phenomenon that describes employees who work only according to their formal job descriptions without emotional involvement or additional contributions. This phenomenon frequently occurs among Generation Z, who have high expectations for job satisfaction. Job satisfaction is believed to play a role in reducing the tendency toward quiet quitting. This study aims to examine the relationship between job satisfaction and quiet quitting among Generation Z employees. The research used a quantitative correlational method involving 113 Generation Z employees aged 18–28 years, selected through purposive sampling. The instruments used include a job satisfaction scale and a quiet quitting scale. The results show a significant negative correlation between job satisfaction and quiet quitting (r = -0.482, p < 0.01). This indicates that the higher the job satisfaction, the lower the tendency for quiet quitting among Generation Z employees. Keywords : Generation z, Job Satisfaction, Quiet Quitting behavior Abstrak Quiet quitting adalah fenomena kerja yang menggambarkan perilaku karyawan hanya bekerja sesuai tugas formal tanpa keterlibatan atau kontribusi lebih. Fenomena ini kerap terjadi pada Generasi Z yang memiliki ekspektasi tinggi terhadap kepuasan kerja. Kepuasan kerja diyakini berperan dalam mencegah kecenderungan quiet quitting. Penelitian ini tujuannya guna memahami hubungan diantara kepuasan kerja dan quiet quitting atas karyawan Generasi Z. Metode penelitian yang digunakan adalah kuantitatif korelasional dengan melibatkan 113 responden karyawan Generasi Z dengan rentang umur 18-28 tahun. Pengambilan sampel secara purposive sampling. Alat ukur yang dipakai meliputi skala kepuasan kerja dan skala quiet quitting. Hasil analisis menunjukkan ada korelasi negatif yang signifikan antara kepuasan kerja dan quiet quitting (r = -0,482, p<0,01). Artinya, semakin tinggi kepuasan kerja, maka semakin rendah kecenderungan quiet quitting pada karyawan Generasi Z. Kata Kunci : Generasi Z, Kepuasan kerja, Quiet Quitting